DIBALIK KEBERLANJUTAN SAWIT: AKTOR, ALIANSI DALAM EKONOMI POLITIK SERTIFIKASI UNI EROPA - Erwiza Erman (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2017)
Environmental sustainability and social justice are the two key principles of global oil palm certification (RSPO) that the country of export of palm oil to the European Union (EU) must adhere to. Therefore, the success or failure of palm oil trade from Indonesia and Malaysia to the EU depends on the fulfillment of these criteria. In reality, the issue of fulfilling these criteria has become an ‘entrance’ for international civil society movements to launch a black campaign in the European Union. This article tries to explain the role of actors and their alliances in palm oil producing countries, Indonesia and Malaysia in response to the implementation of the RSPO and black campaigns in Europe. Combining literary studies and in-depth interviews, this study shows that actors from palmoil producing countries have a strong role in the bargaining process to get the RSPO certificate. They are very active in giving criticism to the RSPO’s weaknesses, and even establish counter-certificates, in Indonesia called ISPO and in Malaysia with MSPO. Behind the issue of unsustainability and social injustice as principal elementsof global certification, there is trade competition between palm oil producing countries and countries in European Union that produce vegetable oils such as sunflower and rapeseed oils.Keywords: certificates, actors, alliances, trade, palm oil, European Union ABSTRAKKeberlanjutan lingkungan dan keadilan sosial adalah dua prinsip utama dalam sertifikasi sawit global (RSPO) yang harus dipatuhi oleh negara eksportir minyak kelapa sawit ke Uni Eropa. Oleh karena itu, sukses atau tidaknya perdagangan sawit dari Indonesia dan Malaysia ke Uni Eropa bergantung pada pemenuhan kriteria tersebut. Dalam kenyataannya, persoalan pemenuhan kriteria tersebut menjadi “pintu masuk” bagi gerakan masyarakat sipilinternasional untuk melakukan kampanye hitam di Uni Eropa. Tulisan ini mencoba menjelaskan peran aktor dan aliansi di negara produsen sawit, Indonesia dan Malaysia, dalam merespons pelaksanaan RSPO dan kampanye hitam di Eropa. Dengan menggabungkan studi kepustakaan dan wawancara mendalam, studi ini memperlihatkan bahwa aktor-aktor dari negara produsen minyak sawit memiliki peranan yang kuat dalam proses tawar-menawar dalam pelaksanaan RSPO. Mereka memberikan kritik yang tajam terhadap kelemahan-kelemahan RSPO dan secaraaktif membentuk sertifikat tandingan, di Indonesia disebut ISPO, sedangkan di Malaysia MSPO. Di balik persoalan ketidakberlanjutan dan ketidakadilan sosial yang menjadi prinsip dasar sertifikasi global, terdapat persaingan dagang antara negara produsen minyak nabati sawit dan negara-negara di Uni Eropa yang memproduksi minyak nabati seperti dari bunga matahari dan rapeseed.Kata kunci: sertifikat, aktor, sawit, perdagangan, Uni Eropa